Cardiac Troponin Levels In COPD Cases - Deveci, Figen; Turgut, Teyfik; Tug, Tuncer; Kirkil, Gamze; Turkoglu, Suat; Muz, Mehmet Hamdi (Bilimsel Tip Publishing House, 2006)
It is determined that cardiac troponin (CT) levels that is specific marker for myocardial injury, can increase in COPD attacks. We aimed to investigate the serum CT levels of acute and stabilized COPD cases, and relation between pulmonary function parameters (PFP) and arterial blood analyses (ABA) with CT. Demographic characteristics, PFP, ABA, electrocardiographic (ECG) and echocardiographic properties of 27 cases with COPD attack (group 1) and 13 stabilized COPD (group 2) and 10 healthy controls cases were determined. Serum troponin I (sTnI) and creatinin cinase-MB levels of all cases were evaluated. Levels above 0.5 ng/ml for sTnI were accepted as high levels. SaO2, and FEV1/FVC ratio were significantly lower in group 1 than group 2 (p=0.000, p=0.029, respectively). sTnI levels were high in group 1 compared with group 2 (p=0.017) and 3 (p=0.000), and sTnI levels were statistically high in group 2 compared with group 3 (p=0.000). sTnI levels were above 0.5 ng/ml in 9 cases of group 1, no elevation was seen in group 2. Seven of 9 cases had pathological ECG properties (ST depression, ST elevation, T changes, block). No relation was observed between sTnI levels and PFP, ABA. We determined that serum troponin I levels increased in COPD attacks, but have no relation between pulmonary functions and oxygenation.
Keywords: COPD; cardiac troponin I; respiratory function test; arterial blood gases